4-TO-5-YEAR OLD CHILDREN SPEAKING ABILITY THROUGH CONSTRUCTIVE PLAY WITH PEER GROUP AT BON THORIF KINDERGARTEN IN PALEMBANG - SRI SUMARNI (Sriwijaya University Learning and Education International Conference, 2016)
were from 4 to 5 through constructive play with peer group. The research was carried out at BonThorif Kindergarten in Palembang. The method was classroom action research from Kemmis andTaggart which consisted of planning, treatment, observation, and reflection. The treatments wereconducted in 2 cycles and each cycle consisted of six treatments. The subjects of the research were 18pupils whose ages were from 4 to 5 at Bon Thorif Kindergarten in Palembang. The data were analyzedquantitatively and qualitatively. The quantitative analysis showed pupils’ speaking ability wasimproved from pre-treatments to the second cycle which was 82.2%. This showed the treatment’ssuccess with 75% improvement. It indicates that the reserach was successful. The qualitative analysisby using a model proposed by Miles and Huberman with triangulation was also carried out consisting:(1) data reduction; (2) data display; and (3) verification, through observation, interview, anddocumentation during the treatment. The result revealed that constructive play with peer group couldimprove pupil’s speaking ability. Through some experiences in playing, having recreation, andinteracting with peer group, all aspects of pupils’ speaking ability were improved.